Koperasi simpan pinjam: Solusi untuk mengatasi keterbatasan akses keuangan - PUTRI, WILDA AMELIA (Maliki Interdisciplinary Journal, 2025)
Savings and Loan Cooperatives (KSP) are financial institutions based on the principles of mutual cooperation, justice, and independence, aiming to improve the welfare of their members through easy and affordable savings and loan services. KSPs are crucial in expanding financial access for marginalized communities. Their advantages include competitive interest rates, fast processing, active member participation, and protection from loan sharks. Despite facing operational and technological challenges, KSPs have significant potential to grow through digitalization and innovation. With their adaptive principles, KSPs serve as pillars of the people's economy, supporting MSMEs and driving local economic growth. To achieve their full potential, KSPs need to strengthen transparent governance, improve members' financial literacy, and adopt digital technology in their financial management systems. Digitalization enables KSPs to provide more efficient services, from recording transactions to providing app-based loans, thus facilitating member access in the modern era. Furthermore, collaboration with other financial institutions and government policy support are crucial factors in expanding KSPs' reach and competitiveness. With professional and innovative management, KSPs function not only as financial institutions but also as a means of sustainable community economic empowerment.